Person–Organization Fit and Public Service Motivation in the Context of Change. Issue 5 (27th May 2016) - Teo, Stephen T. T.; Pick, David; Xerri, Matthew; Newton, Cameron
Abstract: This study examines public sector change, motivation and person–organization (P–O) fit in a stress context. The results provide empirical evidence that change initiatives produce change-induced stressors. However, change processes, including participation in change decision-making and the provision of change information, increase public service motivation, reduce change-induced stressors and ultimately improve P–O fit and job satisfaction. The results also depict that, in the context of change, public service motivation positively influences job satisfaction, with this relationship partially mediated by P–O fit. Implications for New Public Management and the importance of change processes for reducing workplace stress are discussed.